Reliability of Protein Abundance and Synthesis Measurements in Human Skeletal Muscle. Issue 7 (6th December 2019) - Srisawat, Kanchana; Hesketh, Katie; Cocks, Matt; Strauss, Juliette; Edwards, Ben J.; Lisboa, Paulo J.; Shepherd, Sam; Burniston, Jatin G.
Abstract: The repeatability of dynamic proteome profiling (DPP), which is a novel technique for measuring the relative abundance (ABD) and fractional synthesis rate (FSR) of proteins in humans, is investigated. LC–MS analysis is performed on muscle samples taken from male participants ( n = 4) that consumed 4 × 50 mL doses of deuterium oxide ( 2 H2 O) per day for 14 days. ABD is measured by label‐free quantitation and FSR is calculated from time‐dependent changes in peptide mass isotopomer abundances. One‐hundred one proteins have at least one unique peptide and are used in the assessment of protein ABD. Fifty‐four of these proteins meet more stringent criteria and are used in the assessment of FSR data. The median (M), lower‐, (Q1 ) and upper‐quartile (Q3 ) values for protein FSR (%/d) are M = 1.63, Q1 = 1.07, and Q3 = 3.24, respectively. The technical CV of ABD data has a median value of 3.6% (Q1 1.7% to Q3 6.7%), whereas the median CV of FSR data is 10.1% (Q1 3.5% to Q3 16.5%). These values compare favorably against other assessments of technical repeatability of proteomics data, which often set a CV of 20% as the upper bound of acceptability.